Regulation of transcription factors by Tumor-Specific MAGE proteins - Laiseca, Julieta Eva (2015)
The tumor specific melanoma antigen gene (MAGE-I) family was initially considered promising and selective targets for immunotherapy. Currently, their functional characterization points to a role in transcription regulation. In this article we focus on MAGE-A proteins as regulators of transcription factors involved in different cancer-related pathways and how this regulation could contribute to tumorigenesis.